2021
DOI: 10.1186/s12891-020-03923-w
|View full text |Cite
|
Sign up to set email alerts
|

In vitro elution characteristics of gentamicin-impregnated Polymethylmethacrylate: premixed with a second powder vs. liquid Lyophilization

Abstract: Background Antibiotic-loaded bone cement, or antibiotic-impregnated polymethylmethacrylate (PMMA), were developed to prevent and treat bone and joint infections. Gentamicin is an antibiotic that is commonly used in combination with PMMA; however, gentamicin powder is hard to obtain in many countries. This study aimed to evaluate the elution characteristics of gentamicin-impregnated PMMA made with lyophilized liquid gentamicin, compared with PMMA; which is made from commercial gentamicin powder.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Regardless of this study's findings, it is essential to acknowledge delivery vehicles, types of antibiotics, dosage recommendations, indications, and tribological and mechanical properties when preparing antibiotic-loaded spacers or bone cement [20,21]. There is a difference in elution between powdered antibiotics and liquid antibiotics [22,23].…”
Section: Discussionmentioning
confidence: 91%
“…Regardless of this study's findings, it is essential to acknowledge delivery vehicles, types of antibiotics, dosage recommendations, indications, and tribological and mechanical properties when preparing antibiotic-loaded spacers or bone cement [20,21]. There is a difference in elution between powdered antibiotics and liquid antibiotics [22,23].…”
Section: Discussionmentioning
confidence: 91%
“…Liawrungrueang, W. et al; aimed to evaluate the elution characteristics of gentamicin-impregnated PMMA made with lyophilized liquid gentamicin, which was compared with PMMA; which was made from commercial gentamicin powder. This study concluded that the Gentamicin-impregnated PMMA made with lyophilized liquid gentamicin showed a higher rate of antibiotic elution in preliminary in vitro studies when compared with PMMA made with premixed gentamicin powder 86 .…”
Section: Introductionmentioning
confidence: 84%
“…Recent third generation antibiotic-impregnated PMMA spacer are able to provide a high concentration of antibiotics at the site of infections. 35 In recent years, material technology developments have offered several options for an improved and prolonged antibiotic pharmacokinetic released profile. It was the aim of this study to assess whether third generation antibiotic-impregnated PMMA spacer Stage-One select would exhibit superior antibiotic release profiles as compared of a gentamicin burst release, there is plateau phase with a significant lower prolonged release of gentamicin.…”
Section: Discussionmentioning
confidence: 99%
“…However, since there is a limited number of studies of prolonged antibiotic release concentrations, the current evidence regarding these concentrations should be interpreted with care. Recent third generation antibiotic‐impregnated PMMA spacer are able to provide a high concentration of antibiotics at the site of infections 35 . In recent years, material technology developments have offered several options for an improved and prolonged antibiotic pharmacokinetic released profile.…”
Section: Discussionmentioning
confidence: 99%